Literasi Keuangan: Menjelajahi Dunia Kartu Kredit Dan Kredit Dengan Bijaksana - Puput Iswandyah Raysharie; Yonatan Ari Santoso; Rinto Alexandro; Erni Dwi Puji Setyowati (BADAN PENERBIT STIEPARI PRESS, 2024)
The HR Assistance Lecturer (superior) activity at Palangka Raya University carries out financial literacy education with a focus on the theme